THE USE OF THE JAVANESE GAMELAN AS MEDIUM OF CULTURAL HERITAGE AT GKJ GONDOKUSUMAN YOGYAKARTA - Krisno Utomo, Yunatan; Sumaryono, Totok; Rohendi Rohidi, Tjetjep; Ganap, Victor (International Journal of Psychosocial Rehabilitation, 2024)
The background to the study of the use of Javanese gamelan as a cultural heritagemedium in Javanese Christian Church (GKJ) Gondokusuman is the church’sawareness of the importance of cultural conservation for religious people who live ina socio-cultural environment.The purpose of this study is to analyze the use ofJavanese gamelan as an inheritance of Javanese cultural values in GKJGondokusuman congregation. This study used a qualitative method with aphenomenological research design with an interdisciplinary study approach. Thisstudy found that the use of Javanese gamelan in congregational worship can be amedium for educational inheritance, both spiritual and cultural education. In addition,the practice of gamelan in worship is able to increase appreciation and encouragingthe practice of religious life.The application of art and culture in the context ofworship can be a dynamic force in realizing the education of Javanese people whoare both religious and also cultured.